Juridical Analysis Of The Responsibilities Of Notaries In Making Deeds Of Statement Of General Meeting Decisions Shareholders Of Limited Liability Companies - Novalina Estetika Sinaga; Laily Wahliati; Markus Gunawan; Erniyanti Erniyanti; Soerya Respationo (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
Notaries must pay attention in detail that the recipient of the power of attorney is indeed a representative of the Limited Liability Company (PT) concerned who is authorized and has the ability to make the deed.9 The form of the PKR is a notarial deed, but the deed is the result of a meeting decision made by the minutes under hand. Based on Article 21 Paragraph (4) of the UUPT which states that it is permissible for a PKR deed to be made by a notary in the form of an authentic deed. If there is a formal defect in the deed, the deed only has the force of evidence like a private deed if the parties sign the deed. In accordance with Article 21 Paragraph (4) of the UUPT. The conclusion is a limited liability company, hereinafter referred to as a company, is a legal entity which is a capital association, established based on an agreement, carrying out business activities with authorized capital which is entirely divided into shares and fulfilling the requirements stipulated in the law and its implementing regulations. This definition is based on the provisions of Article 1 number (1) of Law Number 40 of 2007 concerning Limited Liability Companies (UUPT). Verification of Authority, Notary must ensure that the limited company meeting is attended by parties authorized to represent the company. This includes checking the validity of the power of attorney or other documents showing the authority of the parties present at the meeting. Parties' Lack of Understanding of Legal Procedures and Obligations.